Student evaluation on educator’s teaching: a retrospective study at Kolej Kemahiran Tinggi Mara Sri Gading (KKTMSG), Batu Pahat, Johor - Yusof, Yusliandy (2022)
Student Evaluation on the Educator’s Teaching is a well-known method in higher learning institutions for student to evaluate their educator. This method is commonly known as a Student Evaluation of Teaching (SET). However, there have been different conclusion on how personality and ability characteristics were used to describe effective teaching. There is insufficient studies regarding the criteria that influence Student Overall Rating (SOR). Furthermore, results from the previous study is unable to accommodate with Kolej Kemahiran Tinggi MARA Sri Gading (KKTMSG) teaching environment where the data obtained was inefficiently analysed, interpreted, visualized, and acted upon. This study aims to explore the relationship between SET and an educator’s performance, along with the motivation that encourage knowledge delivery. The research design is a retrospective study where existing data is used. The population of this study is the student’s data collection consisting of the SET data from 36,762 students who studied at KKTMSG from 2015 to 2019. The descriptive statistics analysis includes mean, standard deviation, frequency, and percentage, while inferential statistics analysis includes correlation analysis and Friedman Test. As an outcome, there is correlation for all criteria with Type of Rating, and students give a higher rating for instructors who are excellent in the teaching compared to the personality. This in turn, could motivate the instructor to improve their teaching style.